Hubungan antara Kemandirian Emosi dengan Motivasi Belajar - Solita, Lusiana; Syahniar, .; Nurfarhanah, . (Konselor, 2012)
Abstract, Emotional independence is one of the most important in the motivation to learn as emotion plays an important role in encouraging a sense of self and mental activities that can foster the spirit of learning .. This research is a descriptive correlational aimed to examine the relationship between adolescent emotional autonomy motivation to learn in high school Adabiah Padang. From the results of the study show that there is a significant relationship between emotional independence and motivation to learn is at a level strong enough.